Bioactive Nanofibres for Wound Healing Applications (Journal of Fiber Bioengineering and Informatics, 2018)
This study investigates carbon nanotube textiles as advanced personal protection equipment forfirefighters and first responders. Carbon nanotubes are lightweight, flame resistant, and possess highmechanical and thermal properties. Carbon nanotubes are also thermally anisotropic, meaning theyeasily conduct heat along the axis of an individual tube, and are relatively insulating across the tube'sdiameter. By recognizing this anisotropic behavior, heat transfer through a layer of aligned carbonnanotubes in a garment can be partially redirected to a cold reservoir thereby protecting the wearerfrom heat stress and exhaustion. Finite element models were developed to simulate a carbon nanotubelayer embedded in a firefighting garment and thermally connected to a cold reservoir. Simulation showedthat under heat stress conditions, firefighter skin temperature was considerably reduced by the coolinglayer.